A SHORT NOTE ON FIBONACCI NUMBERS IN A GENERALIZED PYTHAGOREAN TRIPLES - Emily L Casinillo; Leomarich F Casinillo (Journal of Fundamental Mathematics and Applications (JFMA), 2021)
This paper aims to construct a new formula that generates a Fibonacci numbers in a generalized Pythagorean triples. In addition, the paper formulates some Fibonacci identities and discuss some important findings.